If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=-3/7(x)
We move all terms to the left:
12-(-3/7(x))=0
Domain of the equation: 7x)!=0We get rid of parentheses
x!=0/1
x!=0
x∈R
3/7x+12=0
We multiply all the terms by the denominator
12*7x+3=0
Wy multiply elements
84x+3=0
We move all terms containing x to the left, all other terms to the right
84x=-3
x=-3/84
x=-1/28
| 8(x-1)=6x+3 | | 4x-52=11x+123 | | -x/11=-3 | | x^2-11x=18=0 | | 11=5(x-30 | | x/13=-3 | | 4(x-3)=-3x | | -x-111=-10x+114 | | 84.78=3.14*r^2*9 | | 10k–1=k–43 | | r/4=7/5 | | -1/4x+5=3 | | -192-2x=51+7x | | 2(5x+8)=5(3x-17)+16 | | -3(c+)-4c=60 | | -2+x/3=4 | | -6(x+3)=-18 | | -74-3x=-7x+26 | | -53=-8x+3 | | -4(n-1)=0 | | 7x+7=-x-1 | | -3(n-12)=0 | | 2x+12x=154 | | -21+2x=-x+33 | | 9x-15=10x+12 | | -15+7x=5x+19 | | -4x=2x=36 | | 2x+6=2x+8 | | 2x+6=2x+6 | | 3x-4)=-3 | | t(t+-24)=-100 | | 2+21a=11a^2 |